2024
DOI: 10.17485/ijst/v17i4.2843
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Image Processing Analysis on Polypropylene Fiber Reinforced Foamed Concrete

R Prakash,
N Divyah,
V Selvapriya
et al.

Abstract: Objectives:The research explores the effect of adding polypropylene fiber in foamed concrete. Methods/Analysis: The manuscript discusses the mechanical and durability properties of polypropylene fiber reinforced foamed concrete. Fly ash, copper slag, and polypropylene fiber were admixed for strengthening the foamed concrete. The experimental analysis is carried out with polypropylene fibers at 0%, 0.25%, 0.5% and 0.75% by volume of concrete. Image processing analysis through MATLAB was done to validate the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it has been demonstrated that adding natural fibers like basalt improves mechanical characteristics and impact resistance (8) , albeit with certain restrictions on compressive strength (9) . The effectiveness of several fibers, such as steel (10) , basalt (11) , and polypropylene (12) , in enhancing the toughness, ductility, and energy absorption capacity of concrete after cracking has been studied. This paper aims to give insights into the best way to include fibers to obtain improved performance of sintered flyash LWAC in structural applications by a thorough study of the literature and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that adding natural fibers like basalt improves mechanical characteristics and impact resistance (8) , albeit with certain restrictions on compressive strength (9) . The effectiveness of several fibers, such as steel (10) , basalt (11) , and polypropylene (12) , in enhancing the toughness, ductility, and energy absorption capacity of concrete after cracking has been studied. This paper aims to give insights into the best way to include fibers to obtain improved performance of sintered flyash LWAC in structural applications by a thorough study of the literature and experimental results.…”
Section: Introductionmentioning
confidence: 99%